Proposta da matriz maturidade para o desenvolvimento do lean six sigma em organizações - Regis, Camila Tavares [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
As long as globalization advances, organizations than were previously competing with a local market - or at most, national - find themselves competing with large multinationals in different countries nowadays. In order to survive in this competitive environment, companies need to improve their production processes and to reduce their product costs increasingly as well as their production costs in order to improve the bottom line as a whole. One of the many tools for improvements in the production process is the Lean Six Sigma, a set of principles and practices that seeks to reduce process variability and improve the organization's results. The maturity matrix is another quality tool that evaluates the development of the organization in different aspects and provides an overview of the level of development at each stage, pointing positive points that should be strengthened and weaknesses that should be improved. The work in question proposes a maturity matrix to assess the degree of implementation of Lean Six Sigma tool in organizations, in order to make possible the creation of action plans necessary to align and improve the use of these principles within organizations. For this, a study of the principles of Lean Manufacturing and Six Sigma was made and from the synergy between these two philosophies, principles of Lean Six Sigma were defined and then transported to a maturity matrix. The maturity matrix proposed is a simple method of diagnosing the degree of maturity of Lean Six Sigma within organizations that allows the correct analysis of the organization, so that appropriate actions propositions are made for better implementation of Lean Six Sigma

Com o avanço da globalização, organizações que antes se encontravam concorrendo com um mercado local - ou no máximo, nacional - agora se encontram concorrendo com grandes multinacionais instaladas em diferentes países. Para sobreviver nesse cenário competitivo, as empresas precisam cada vez mais melhorar seu processo produtivo e reduzir os seus custos de produto, bem como os seus custos de produção, a fim de melhorar o resultado final como um todo. Uma das ferramentas para a melhoria do processo produtivo é o Lean Six Sigma, um conjunto de princípios e praticas que visa reduzir a variabilidade do processo e melhorar os resultados da organização. A matriz maturidade é outra ferramenta da qualidade que avalia o desenvolvimento da organização em diferentes aspectos e proporciona uma visão geral do grau de desenvolvimento de cada estágio, apontando pontos positivos que devem ser reforçados e pontos negativos que devem ser melhorados. O trabalho em questão propõe uma matriz maturidade para avaliar o grau de implementação da ferramenta Lean Six Sigma nas organizações, de modo a tornar possível a criação de planos de ações necessárias para alinhar e melhorar o uso desses princípios dentro das organizações. Para isso, foi feito um estudo acerca dos princípios do Lean Manufacturing e do Six Sigma e, a partir da sinergia entre essas duas filosofias, foram definidos princípios do Lean Six Sigma que foram transportados para uma matriz maturidade. A matriz maturidade proposta é um método simples de diagnóstico do grau de maturidade do Lean Six Sigma dentro das organizações que permite a correta análise da organização, para que sejam feitas proposições de ações adequadas para uma melhor aplicação do Lean Six Sigma
Keywords: Gestão da qualidade total; Seis sigma (Padrão de controle de qualidade); Produção enxuta; Total quality management